2017
DOI: 10.1007/s10764-017-9997-2
|View full text |Cite
|
Sign up to set email alerts
|

Sleeping and Ranging Behavior of the Sambirano Mouse Lemur, Microcebus sambiranensis

Abstract: Primates require secure sleeping sites for periods of rest, but despite their importance, the characteristics of desired sleeping sites are poorly known. Here we investigated the sleeping ecology of a radio-collared population of the Sambirano mouse lemur, Microcebus sambiranensis, during the nonreproductive season in the Anabohazo forest, northwestern Madagascar. We also investigated their ranging behavior and examined the spatial distribution of sleeping sites within the home ranges of the collared individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 48 publications
0
9
1
Order By: Relevance
“…It is also possible that our observations were the result of accidental disturbance of sleeping sites. However, we do not believe this was the case for our observations, as three other nocturnal lemur species are abundant at this study site (Hending et al, 2017) and we never observed daytime activity in these three species. Another possible ultimate reason for our observations is that M. zaza may minimize predation risk via temporal crypticity (Curtis & Rasmussen, 2006;Colquhoun, 2007;Tattersall, 2008), as they are small-bodied and therefore vulnerable to aerial and terrestrial predators (both diurnal and nocturnal) that are common within the National Park (Randriatahina & Volampeno, 2012).…”
Section: Observationscontrasting
confidence: 56%
“…It is also possible that our observations were the result of accidental disturbance of sleeping sites. However, we do not believe this was the case for our observations, as three other nocturnal lemur species are abundant at this study site (Hending et al, 2017) and we never observed daytime activity in these three species. Another possible ultimate reason for our observations is that M. zaza may minimize predation risk via temporal crypticity (Curtis & Rasmussen, 2006;Colquhoun, 2007;Tattersall, 2008), as they are small-bodied and therefore vulnerable to aerial and terrestrial predators (both diurnal and nocturnal) that are common within the National Park (Randriatahina & Volampeno, 2012).…”
Section: Observationscontrasting
confidence: 56%
“…Cheirogaleus may be sensitive to habitat degradation and edge-effects (Lehman et al, 2006;but see Hending, 2021), and the population density of C. medius in SIRNP may be limited by the ongoing forest degradation that is typical of the region (Seiler et al, 2010); this also may explain the differences in density between Anabohazo (a continuous forest) and Ankarafa (a highlydegraded and fragmented forest). Furthermore, C. medius lives sympatrically with the northern giant mouse lemur (Mirza zaza), the Sambirano mouse lemur (Microcebus sambiranensis), and the Sahamalaza sportive lemur (Lepilemur sahamalaza) in SIRNP (Hending et al, 2017c(Hending et al, , 2022a. Although niche separation exists between these species, all four of these taxa require secure sleeping sites.…”
Section: Population Density and Sizementioning
confidence: 99%
“…A total of 24 mouse lemur species have so far been described [28]. The social system of many of these species has not yet been studied, and current knowledge is largely based on the study of seven species only ( M. berthae , M. griseorufus , M. lehilahytsara , M. murinus , Microcebus ravelobensis , M. rufus , M. sambiranensis ), most of which form some kind of sleeping groups (male–male, male–female, or female–female) during daytime in a shelter, at least temporarily, and have non-exclusive, largely overlapping home ranges not only with members of the same sleeping group but also with male strangers [reviewed in 11, 13, 29, 30]. However, based on extensive nocturnal survey work that has been conducted in many locations across Madagascar, it is evident that probably all mouse lemur species live in dispersed neighborhood systems [31], as it is typically single individuals and not groups that are encountered during the night [3235].…”
Section: Introductionmentioning
confidence: 99%